FORMULASI CINCAU JELLY DRINK (Premna oblongifolia L Merr) SEBAGAI PANGAN FUNGSIONAL SUMBER ANTIOKSIDAN - Khoiriyah, Nur; Amalia, Leily (Jurnal Gizi dan Pangan, 2014)
The objectives of this study were to make formulation of jelly drink product made from clump cincau leaf (Premna oblongifolia L Merr), to analyze hedonic and hedonic quality of the formulas, to analyze nutrient, fiber, and total phenol contents and antioxidative activity of the selected formula. The formulation was made to be three formulas, namely formula 1 (0.3% of carrageenan), formula 2 (0.4% of carrageenan), and formula 3 (0.5% of carrageenan). Ranking score showed the selected formula was the formula 1 (0.3% of carrageenan). Nutrient content of the selected formula showed that water, ash, protein, fat and carbohydrate level were 98.54%, 0.29%, 0.13%, 0.10%, and 0.95% (wet basis) respectively. The total dietary fiber content of the selected formula was 2%, comprised of soluble 1.1% and insoluble dietary fiber 0.9%. The total phenol of the selected formula was 78.32 mg GAE/100g. Antioxidant activity of cincau jelly drink product which indicated by IC50 value was 1 045 μL, which is categorized as strong inhibitation capacity. The acceptance of the formula by consumers was 69.07% and it is categorized as moderate acceptance, with the most preference attribute was melon aroma.